Purchase order for supply, installation & commissioning of the fire suppression system of the data center and IT racks in BRACU new campus building - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Signal Technology & Engineering Ltd. for supply, installation & commissioning of the fire suppression system of the data center and IT racks in BRACU new campus building.